2021
DOI: 10.1007/s13205-020-02601-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide identification and expression analysis of pepper C2H2 zinc finger transcription factors in response to anthracnose pathogen Colletotrichum truncatum

Abstract: Although, the C 2 H 2 zinc finger (ZF) family of plant transcription factors have been implicated in multiple biological processes, they are yet to be characterized in the economically important chilli pepper (Capsicum annuum). In this study, a total of 79 C 2 H 2 ZF genes were identified in the pepper genome. Phylogenetic analysis categorized the pepper C 2 H 2 ZF (CaZF) members into five subfamilies each with unique conserved domains and functions. Genomic organization revealed that CaZF genes have variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 60 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…The latter have been described to facilitate hypersensitive cell death response in tobacco and tomato (Van Den Burg et al 2008) and shown to be involved in defense response to stripe rust in wheat (Yin et al 2018). On the other hand, Zinc fingers of the C2H2-type were linked to plant defense response (Kim et al 2004; Tian et al 2010; Yin et al 2020; Sharma et al 2021), where some cases have shown that the transcriptional repression activity of the zinc finger was the mechanism behind this association (Weigel et al 2005; Uehara et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter have been described to facilitate hypersensitive cell death response in tobacco and tomato (Van Den Burg et al 2008) and shown to be involved in defense response to stripe rust in wheat (Yin et al 2018). On the other hand, Zinc fingers of the C2H2-type were linked to plant defense response (Kim et al 2004; Tian et al 2010; Yin et al 2020; Sharma et al 2021), where some cases have shown that the transcriptional repression activity of the zinc finger was the mechanism behind this association (Weigel et al 2005; Uehara et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another associated region was detected on chromosome 5AL contained candidate genes putatively encoding C2H2-type Zinc fingers, an MLO-related protein, a serine/threonine kinase and an NLR. Zinc fingers of the C2H2-type were linked to plant defense response (146)(147)(148)(149), where some cases have shown that the transcriptional repression activity of the zinc finger was the mechanism behind this association (150,151). Mlo is a well-known player in powdery mildew resistance in barley, with rice and wheat homologs shown to have a conserved function (152,153).…”
Section: Gwas Of the Complete Landraceplus Panel Detects Known Pm Gen...mentioning
confidence: 99%
“…C2H2 ZFPs are one of the most extensively studied transcription factors that play crucial roles in many biological processes in eukaryotic organisms [6,21]. The Q−type ZFP, a plant-specific subfamily of C2H2−ZFPs, was found to be involved in plant development, as well as various stress responses [15,34,51]. So far, Q−type ZFPs have been extensively studied in many species, such as A. thaliana, S. lycopersicum, Solanum tuberosum, T. aestivum, O. sativa, and P. trichocarpa (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, C 2 H 2 zinc finger transcription factor (TF) genes were identified, and their expression levels in diseased pepper were analyzed to further clarify how the pepper response to anthracnose is regulated [ 15 ]. Using CRISPR/Cas9 technology to knock out CaERF28 can significantly increase the resistance of pepper to Colletotrichum truncatum [ 16 ].…”
Section: Introductionmentioning
confidence: 99%